2015
DOI: 10.1016/j.cell.2015.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Origin of Postnatal Neural Stem Cells

Abstract: Adult neural stem/progenitor (B1) cells within the walls of the lateral ventricles generate different types of neurons for the olfactory bulb (OB). The location of B1 cells determines the types of OB neurons they generate. Here we show that the majority of mouse B1 cell precursors are produced between embryonic days (E) 13.5 and 15.5, and remain largely quiescent until they become reactivated postnatally. Using a retroviral library carrying over 100,000 genetic tags, we found that B1 cells share a common proge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
399
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 406 publications
(449 citation statements)
references
References 54 publications
22
399
3
1
Order By: Relevance
“…The prevailing model suggested that radial glia transform, after they produce neurons and glia in the embryo, into B1 cells (Kriegstein and Alvarez-Buylla 2009). This simple view is challenged by a recent lineage tracing study that investigates the pedigree of adult B1 cells (Fuentealba et al 2015). The new results show that postnatal B1 cells are indeed derived from embryonic NSCs that produce also neurons and glia for other forebrain regions (including cortex, striatum, and septum).…”
Section: The Search For Markers Of Type B1 Cellsmentioning
confidence: 71%
“…The prevailing model suggested that radial glia transform, after they produce neurons and glia in the embryo, into B1 cells (Kriegstein and Alvarez-Buylla 2009). This simple view is challenged by a recent lineage tracing study that investigates the pedigree of adult B1 cells (Fuentealba et al 2015). The new results show that postnatal B1 cells are indeed derived from embryonic NSCs that produce also neurons and glia for other forebrain regions (including cortex, striatum, and septum).…”
Section: The Search For Markers Of Type B1 Cellsmentioning
confidence: 71%
“…For other datasets, differing in the number or identity of the sampled tissues, there may be less of an a priori expectation for the shape of the ontogenetic phylogeny. While there is a general understanding of the major divisions of tissues during development, the embryonic origins and lineage of somatic germ cell populations are not straightforward and still being established (e.g., Romagnani et al, 2015;Fuentealba et al, 2015;Boisset and Robin, 2012). The current model could easily be extended to ontogenetic phylogenies for families with two or more offspring.…”
Section: Discussionmentioning
confidence: 99%
“…spiral ganglion, vestibular epithelium or OC. Potency of neural stem cells has been difficult to determine without adequate markers to use for tracing the lineage of progenitor cells and for the differentiated progeny, and, as a result, similar questions have remained unresolved in several neural and non-neural stem cell compartments (Fuentealba et al, 2015). Here, by using gene expression analysis and physiological properties, as well as lineage tracing of putative progenitors in the spiral ganglion, OC and vestibular epithelia, we could identify nine distinct cell types, which allowed us to determine whether the progenitor cells were uni-, multi-or pluripotent.…”
Section: Introductionmentioning
confidence: 99%